The role of the patients register in early diagnostics of familial adenomatosis coli - A. M. Kuzminov; A. V. Karpuhin; Yu. Yu. Chubarov; I. Yu. Sachkov; T. A. Savel’yeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy of the Register of patients with familial adenomatosis coli.Material and methods. Overall 1036 patients with familial adenomatosis coli were observed. Of them 117 proposituses with detailed hereditary history taken to the present time, and 118 their natural relatives actively involved in investigation, were included in the Register of family adenomatosis.Results. Presence of the Register of patients with familial adenomatosis coli with subsequent summons and investigation of relatives of proposituses allowed to decrease age of patients at the moment of diagnosis from 30 to 18 years, to reduce number of patients with developed colorectal cancer from 43,6 to 4,9%, to reduce cases of total involvement of the large intestine by polyps from 72 to 5%. Genetic testing detected disease at preclinical stage in 18 (56%) of 32 actively investigated relatives of proposituses, allowed to form the risk group of patients from АРС-negative families and to remove patients who have not inherited АРС (Adenomatous Polyposis Coli) mutation from further observation.Conclusion. Presence of the Register of patients with familial adenomatosis coli promotes early diagnostics, improves of results of treatment and optimize monitoring of this category of patients.